A New Species of Leucheria (Asteraceae, Mutisieae) from Chile - Katinas, Liliana (2008)
A new species of Leucheria Lagasca (Asteraceae, Mutisieae), L. graui Katinas, M. C. Telleria & Crisci, with glutinous habit and yellow corollas is described and illustrated. This would be the only species within Leucheria with yellow corollas. The pollen of the new species is also described and illustrated; it belongs to the Oxyphyllum Philippi pollen type and has similar characteristics to other species of Leucheria. The new species appears to be morphologically close to L. apiifolia Philippi, which belongs to the relatively primitive L. glacialis (Poeppig ex Lessing) Reiche evolutionary line of dry environments.